Cytotoxic activity of seaweeds from North Sulawesi marine waters against cervical cancer - Grace Sanger, Lexy Karel Rarung, Djuhria Wonggo, Verly Dotulong, Lena Jeane Damongilala, Trina Ekawati Tallei (Journal of Applied Pharmaceutical Science, 2021)
Seaweeds are a rich source of bioactive substances with biological activity and potential medicinal applications in the treatment of degenerative diseases such as tumors and cancer. The purpose of this study was to determine the antioxidant and anticervical cancer activity of several seaweeds collected from North Sulawesi marine waters, specifically Gracilaria salicornia, Turbinaria decurrens, Halimeda macroloba, and Laurencia tronoi. To carry out the antitoxicity and antioxidant tests, the seaweeds were extracted using ethanol. The methods used to determine antioxidant activity are total phenolic content (TPC), 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity, and ferric reducing antioxidant power (FRAP). Meanwhile, the determination of anticervical cancer activity was carried out using the 3-(4,5-dimethylthiazol-2-yl)-2-5-diphenyltetrazolium bromide assay by utilizing HeLa (ATCC® CCL-2™) cell lines. HeLa is an immortal cell line that has been used in scientific research, and the research has met medical safety standards for human use. The result showed that L. tronoi exhibited the highest TPC [2.051 ± 0.191 µg gallic acid equivalent/g], DPPH [inhibitory concentration (IC50) 0.48 ± 0.023 mg/ml], and FRAP (17.65 ± 0.71 uM Fe2 +/mg extract) activities. The cytotoxic activity (IC50) of extracts against HeLa cells was 432.63 µg/g for G. salicornia, 41.027 µg/g for T. decurrens, 137.38 µg/g for H. macroloba, and 78.53 µg/g for L. tronoi. On the basis of the IC50 value, it can be concluded that extracts of T. decurrens and L. tronoi were more effective against cervical cancer than other seaweed extracts studied. Overall, the results indicated that L. tronoi possessed greater anticervical cancer and antioxidant activity than the other species, indicating that this species is a good source of bioactive compounds for the prevention and treatment of cervical cancer.
Keywords: Cervical cancer, HeLa cells, antioxidant, seaweed, cytotoxicity, North Sulawesi.